2019
DOI: 10.1103/physrevb.100.184426
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Hall effect of skyrmions enabled using nonmagnetic point contacts

Abstract: P a g e 2 | 18 To enable functional skyrmion-based spintronic devices, the controllable generation and manipulation of skyrmions is essential. While the generation of skyrmions by using a magnetic geometrical constriction has already been demonstrated, this approach is difficult to combine with a subsequent controlled manipulation of skyrmions. The high efficiency of skyrmion generation from magnetic constrictions limits the useful current density, resulting in stochastic skyrmion motion, which may obscure top… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 65 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…Another geometrical control of the creation of the magnetic skyrmions was experimentally done by Z. Wang et al [22], where the magnetic skyrmions are created by electric current pulses in a point-contact geometry. It can be caused by the vorticity-induced Zeeman field since the electric current near the point contact is nonuniform and possibly has nonzero vorticity.…”
Section: Discussionmentioning
confidence: 99%
“…Another geometrical control of the creation of the magnetic skyrmions was experimentally done by Z. Wang et al [22], where the magnetic skyrmions are created by electric current pulses in a point-contact geometry. It can be caused by the vorticity-induced Zeeman field since the electric current near the point contact is nonuniform and possibly has nonzero vorticity.…”
Section: Discussionmentioning
confidence: 99%
“…In bulk systems electrical nucleation has been demonstrated at current densities three magnitudes lower 48 . Hrabec et al showed the first experimentally deterministic nucleation from a non-magnetic point contact driven by the divergence of current lines, heating, and spin accumulation at the tip which results in the local reversal of the magnetic configuration near the tip 49,50 (see Fig. 2(c)).…”
Section: A Nucleationmentioning
confidence: 99%
“…Based on the modified Thiele equation, the skyrmion dynamics driven by the current-induced spin–orbit torques (SOTs) can be described as follows: ,,, bold-italicG × bold-italicv α bold-scriptD · bold-italicv 4 π scriptB · bold-italicj e = 0 …”
mentioning
confidence: 99%
“…Based on the modified Thiele equation, the skyrmion dynamics driven by the current-induced spin–orbit torques (SOTs) can be described as follows: ,,, …”
mentioning
confidence: 99%